DAMPAK PEMBERIAN IMPULS ARUS TERHADAP TINGKAT PERLINDUNGAN ARRESTER TEGANGAN RENDAH - Diah Suwarti Widyastuti; Sugiarto Sugiarto (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2017)
Arrester is a device used to protect equipment and electrical systems against overvoltage that one reason is the surge of lightning. Because lightning is a natural phenomenon that the process can not be predicted about time and magnitude of the impulse currents, and if arrester hit by lightning impulse with high peak current value and than arrester is feared can not operate as it should. This research use three impulse current peak value there are 533.33A (0.03 pu), 3866.6A (0.3 pu) and 6858.7A (0.5 pu) tested at low voltage arresters. The test results shown the highest value of leakage current arrester at a maximum voltage of operation (Uc) after buffeted by the current impulse has a value of leakage current 0,32 mA, 0,33 mA and 0,33 mA respectively, still below 1 mA (corresponding international standard IEC 61643-1 Edition 2.0 03/2005). Based on the value of leakage current, it can be said that the arresters in good condition and have not changed the characteristics of volt-ampere (current leaking still relatively the same) and still have good insulating properties even after the current impulse overwritten. The highest value of residual voltage arresters at the peak impulse voltage 10 kV, 15 kV, 20 kV and 24 kV, is 1124 Volt meaning that the margin has exceeded the limit of endurance voltage VW1 class (1000 Volts) amounted to 112.4%, and not exceed the VW2 (2000 Volt) amounted to 43.5%, according to ISO standard 04-7021.21-2004, arresters can be used to protect the electrical equipment with voltage endurance on VW2 class.